Cleft palate in fetuses: feasibility of early diagnosis by Crystal and Realistic Vue rendering 3D ultrasound technology in the first trimester - Shi, Zhihong; Wen, Huaxuan; Leng, Junhong; Wang, Junjun; Wang, Yuemei; Luo, Dandan; Chen, Zhixuan; Qin, Yue; Liang, Meiling; Tan, Ying; Li, Shengli (Frontiers in Pediatrics, 2023)
Objectives: This study aimed to evaluate the feasibility of direct visualization of normal fetal palate, and detect cleft palate in the first trimester with a novel three-dimensional ultrasound (3D-US), Crystal and Realistic Vue technique (CRV). Methods: 2D images and 3D volumes of healthy and cleft palate fetuses at 11-13+6 weeks were obtained prospectively. 2D ultrasound views included the coronal view of the retronasal triangle and midsagittal view of the face. 3D-CRV views were analyzed by multiplanar mode display. The pregnancy outcomes of all fetuses were determined during followed-up period. Results: In our study, 124 fetuses were recruited, including 100 healthy fetuses and 24 cleft palate fetuses. The cleft palate with lip was observed in 23 fetuses (bilateral in 15, unilateral in 6, median in 2) and one cleft palate was only found in the abnormal group. The bilateral (n=12) and median (n=2) cleft palate with lip and cleft palate alone (n=1) were associated with other anatomical or chromosomal abnormalities, 1 unilateral cleft palate with cleft lip had concomitant NT thickening. In cleft palate fetuses group, 16 fetuses suffered intrauterine death which was associated with other structural or chromosomal abnormalities in 14 fetuses, 7 cases were terminated after consultation and one was delivered at term. The coronal view of retronasal triangle and midsagittal view were easily obtained in all fetuses. 3D-CRV images of palatal parts were clearly obtained in all cases. Unilateral, bilateral and median cleft palate with cleft lip were visually demonstrated and classified by 3D-CRV technique. Conclusion: It is feasible to identify the palate by 3D-CRV in the first trimester in both healthy and cleft palate fetuses. Together with 2D ultrasonography as a complementary diagnostic tool, 3D-CRV is helpful to classify the cleft palate with a reasonable degree of certainty.